Endoscopic Management of Pain in Pancreatic Cancer - Mekaroonkamol, Parit; Willingham, Field F; Chawla, Saurabh (JOP. Journal of the Pancreas, 2015)
Pancreatic cancer is the fourth leading cause of cancer-related death in the United States and one of the leading causes of cancer mortality in the United States. Due to its aggressive behavior and lack of effective therapies, palliation plays a critical role in the management of the disease. Most patients with pancreatic cancer suffer from severe pain, which adversely predicts prognosis and significantly impacts the quality of life. Therefore pain management plays a central role in palliation. Non-steroidal anti-inflammatory drugs and opioid agents are often first line medications in pain management, but they do not target the underlying pathophysiology of pain and their use is limited by adverse effects and dependence. The proposed mechanisms of pain development in pancreatic cancer include neurogenic inflammation and ductal hypertension which may be targeted by endoscopic therapies. Endoscopic ultrasound-guided celiac plexus neurolysis (EUS-CPN) and pancreatic duct stent placement are the two primary endoscopic modalities for palliative management in pancreatic cancer patients with refractory pain. Other endoscopic treatments such as biliary stent placement and enteral stent placement for biliary and duodenal obstruction may also help palliate pain in addition to their role in decompression. This article reviews the existing evidence for these endoscopic interventions for pain management in pancreatic cancer. Image: James B. Williams Medical Education Building, Emory University School of Medicine. Atlanta, GA, USA. (Detail from: Wikinedia Commons. Author: Sinam)